In Pursuit of Excellence in Higher Education : The Proceedings of the Second International Conference on Higher Education - Lertchalolam, Chawalert ; Sinlarat, Paitoon ; Bovomsiri, Varapom (Department of Higher Education Faculty of Education Chulalongkorn University and SEAMEO HIRED, 2020)
The Department of Higher Education, Faculty of Education, Chulalongkom University, and the SEAMEO Regional Institute of Higher Education and Development (SEAMEO RIHED) jointly organized this international conference with an intention to put the topic “excellence in higher education” into perspective. The purpose of the conference was to establish a clearer direction and vision for those involved in higher education, and, in turn, contribute to the goal of achieving excellence in higher education. This conference was also organized to celebrate the 40th anniversary of Faculty of Education, Chulalongkom University, an educational institute locally and internationally recognized as an leading institute of higher education.